CIDEX, SAVLON AND HYDROGEN PEROXIDE: WHICH OF THEM IS MORE EFFECTIVE IN DISINFECTION OF VENTILATOR TUBES - H SOLTANI NEZHAD; A VEISY RAYEGANI; KH ZERAAT KARI; B SOLEYMANI (Journal of Research in Medical Sciences, 2001)
Introduction: Nasocomial infections threat any hospitalized patient, specially in intensive care unit. Incidence of these infections has been reported from 1.9 to more than 25 percent. The most common nasocomial infection in intensive care units (ICU) is pneumonia caused by endotraheal intubation and mechanical ventilation. The best procedure for pneumonia prevention in patients under mechanical ventilation is utilization of suitable and proper techniques for equipment sterilization: The goal of this study is determination and comparison of disinfectant materials (cidex, savlon and hydrogen peroxide) about their effects on incidence and type of mechanical ventilators breathing tubes contamination in intensive care unit.
Methods: This is an experimental trial which was done on three groups of mechanical ventilator breathing tubes. Each group contained 20 samples. These three groups of breathing tubes were disinfected with cidex, savlon and hydrogen peroxide. Samples were obtained from tubes for microbial culture berore and after disinfection. Samples were cultured on blood agar. The results of microbial culturing were compared between three groups.
Results: There was no significant difference between three groups of breathing tubes about microbial types and number of colony counted before disinfection. There was no significant difference between cultured colony numbers in three groups before and after disinfection. Cidex, savlon and hydrogen peroxide could decrease incidence of contamination to 100, 98.09 and 100 percent, respectively.
Discussion: All of tested chemical materials have the same results in disinfection. Hydrogen peroxide has less adverse effect on human and environment than cidex. It is less expensive than cidex. So, we recommend to use this material for disifection of mechanical ventilator berthing tubes.